Strain-Based Evaluation of a Steel Through-Girder Railroad Bridge - Andrew N. Daumueller; David V. Jáuregui (Advances in Civil Engineering)
In the state of New Mexico (USA), passenger rail began in 2008 between Belen and Santa Fe on the Rail Runner, following the acquisition of about 100 miles of existing rail and related infrastructure. Many of the bridges on this route are over 100 years old and contain fatigue prone details. This study focuses on a steel through-girder bridge along this corridor. To accurately evaluate these structures for load carrying capacity and fatigue, an accurate analytical model is required. Accordingly, four models were developed to study the sensitivity of a bridge in New Mexico to floor-system connection fixity and the ballast. A diagnostic load test was also performed to evaluate the accuracy of the finite-element models at locations of maximum moments. Comparisons between the simulated and measured bridge response were made based on strain profiles, peak strains, and Palmgren-Miner’s sums. It was found that the models including the ballast were most accurate. In most cases, the pinned ended models were closer to the measured strains. The floor beams and girders were relatively insensitive to the ballast and end conditions of the floor-system members, whereas the stringers were sensitive to the modeling of the ballast.